WORKSHOP IT PENGENALAN KOMPUTER DAN MICROSOFT OFFICE DI SMP NEGERI 12 REJANG LEBONG DESA BELITAR MUKA - Rido Syahputra; Ridho Irvanda; Sazili (Almaun: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mastery of information and communication technology is a necessity in facing the era of globalization, one of which is computers and Microsoft Office. A computer is a tool that processes data according to procedures that have been formulated. A computer is a piece of hardware that is closely related to technology. Microsoft Word is word processing software, one of the main functions of Microsoft Office is processing and producing data, creating letters, creating presentation slides, storing data, sending emails and others. The aim of this training activity is to provide assistance, introduction to computers and Microsoft Office to students at SMPN 12 Rejang Lebong who don't understand computers and use Microsoft Office software. The activities were carried out in two stages, namely introduction to computer components and Microsoft Office training. As a result of this activity, it is hoped that students at SMP 12 Rejang Lebong will be able to better understand and comprehend computers and Microsoft Office.